2016
DOI: 10.54207/bsmps2000-2016-32l452
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicine for Bites by the Tribes of Srikakulam District, Andhra Pradesh

Abstract: The paper deals with 46 species of plants covering 44 genera and 34 families used for curing bites by the tribes of Srikakulam district, Andhra Pradesh. Cucurbitaceae is the dominant family with 4 species followed by Fabaceae, Caesalpiniaceae, Mimosaceae, Asclepiadaceae, Verbenaceae, Apocynaceae, Loganiaceae, Menispermaceae, Euphorbiaceae with 2 species each and others. Herbs are more (16) followed by trees (11), shrubs (10), climbers (8) and a lone liane. Root is involved in 13 practices followed by whole pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In 1960, Jain started intensive field studies among tribal areas of central India [3][4][5][6][7][8][9]. Ramarao Naidu et al [10] dealt with the ethnomedicobotany of the Srikakulam district and reported 25 plant species belonging to 18 families used by the tribals for curing dental disorders. Rao and Reddi [11] reported 35 tuberous medicinal plant species used for a variety of ailments by certain tribal people of the Visakhapatnam district.…”
Section: Introductionmentioning
confidence: 99%
“…In 1960, Jain started intensive field studies among tribal areas of central India [3][4][5][6][7][8][9]. Ramarao Naidu et al [10] dealt with the ethnomedicobotany of the Srikakulam district and reported 25 plant species belonging to 18 families used by the tribals for curing dental disorders. Rao and Reddi [11] reported 35 tuberous medicinal plant species used for a variety of ailments by certain tribal people of the Visakhapatnam district.…”
Section: Introductionmentioning
confidence: 99%